Formulasi biskuit tinggi protein berbasis tepung sorghum dengan penambahan tepung kacang merah sebagai PMT untuk balita - Atmadja, Taufiq Firdaus Alghifari; Fikrinnisa, Rizka; A’yunin, Nur Arifah Qurota (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Most of the biscuits used as additional food for toddlers in Indonesia are still made from wheat flour; therefore, it is necessary to develop a product made from local food that will reduce dependence on wheat flour. The current high consumption of rice has encouraged various food diversification efforts to avoid dependence on a single commodity. Biscuits combine sorghum with red bean flour to increase their protein content, so they can be an alternative, nutrient-dense complementary food for stunted toddlers.Objectives: This study aimed to determine the formulation and protein content of biscuits. This research consisted of making sorghum and red bean flour and biscuit formulations, as well as analyzing protein and food fiber levels.Methods: The experimental design used in this study was completely randomized Design (CRD). The research was conducted at the Basic Laboratory of the Faculty of Health Sciences, Siliwangi University, and the Food and Nutrition Laboratory, Faculty of Agricultural Technology, Gadjah Mada University. The comparison of the amount of ingredients from wheat flour, sorghum flour and red bean flour studied was F0 (wheat flour 80g), F1 (wheat flour 50g; sorghum flour 3g; red bean flour 10g), F2 (wheat flour 50g; sorghum flour 30g; flour red beans 15g), F3 (wheat flour 50g; sorghum flour 30g; red bean flour 20g) and F4 (wheat flour 80g; sorghum flour 30g) and each uses the same amount of ingredients, namely egg yolk 30g, margarine 60g, powdered sugar 40g and powdered milk 54g. Laboratory results were tested using one-way ANOVA and Duncan's advanced test, with a significance level of 0,05.Results: All formulas have significant differences based on the One Way Anova test and meet the quality of biscuits according to SNI 01-2973-2011. The best formulation with chemical test results is F3 with the highest protein content of 13,75%, water content of 4,71%, ash content of 2,43%, fat content of 26,4% and carbohydrate content of 52,7%.Conclusion: Sorghum and bean biscuits that combine sorghum with red bean flour increase the protein content of biscuits, making them an alternative nutrient-dense complementary food for stunted toddlers.KeywordsSorghum flour, red bean flour, biscuit, complementary food